Entire Functions of Bounded L-Index: Its Zeros and Behavior of Partial Logarithmic Derivatives. (6th November 2017) - Bandura, Andriy; Skaskiv, Oleh
Abstract : In this paper, we obtain new sufficient conditions of boundedness of L -index in joint variables for entire function in C n functions. They give an estimate of maximum modulus of an entire function by its minimum modulus on a skeleton in a polydisc and describe the behavior of all partial logarithmic derivatives and the distribution of zeros. In some sense, the obtained results are new for entire functions of bounded index and l -index in C too. They generalize known results of Fricke, Sheremeta, and Kuzyk.